Kogan’s Attitude Toward Old People: Evaluation of validity and reliability assessment among nursing students in Thailand, Myanmar, and Indonesia - Viliporn Runkawatt; Kanyanat Kerdchuen; Kitsanaporn Tipkanjanaraykha; Kanyarat Ubolwan; Yadchol Tawetanawanich; Chairun Nasirin; Mar Lar Win (Asian Journal for Public Opinion Research, 2016)
Background:Asia is on track to become the region with the most elderly people in the world. The elderly population will reach 922.7 million by the middle of this century. Therefore, they will be cared for by the today’s youth. Negative attitudes toward older people can make adolescents more uncomfortable relating to them.Objectives:The objective of this study was to evaluate validity and reliability of Kogan’s attitude toward old people among nursing students in Thailand, Myanmar, and Indonesia.Methods:Content validation of the 34-item Kogan’s attitude toward old people was examined by three geriatric nursing experts. The reliability was evaluated on 600 nursing students, from nursing colleges in Thailand (200), Myanmar (200), and Indonesia (200).Findings:The attitude scores towards the elderly ranged from 34 to 238. All of the 34 items were found to have significant item-to-total correlations (p< .05). The reliability results were as follows: In Thailand, Cronbach’s alpha was .70 for the total scale, .72 for the positive scale, and .68 for the negative scale. In Myanmar, Cronbach’s alpha was .68 for the total scale, .65 for the positive scale, and .66 for the negative scale. In Indonesia, Cronbach’s alpha was .66 for the total scale, .71 for the positive scale, and .72 for the negative scale.Conclusions:These findings suggest that Kogan’s attitude toward old people is reliable and valid for nursing students from Thailand, Myanmar, and Indonesia. However, Kogan’s attitude toward old people should be revised by these countries, including changing wording on all items for better reliability. The revised version must then be tested for reliability and validity.